Penerapan Aplikasi Accurate Dalam Penyusunan Laporan Keuangan Pada PT Taxand Adi Consultama - Pinandhito, Naufal Hariz; Triandi, Triandi (Jurnal Abdimas Dedikasi Kesatuan, 2024)
A financial report is an important document in the business world that presents financial information about an entity for a certain period. The main purpose of financial reports is to provide a clear and transparent picture of a company's financial position, financial performance and cash flow to stakeholders such as owners, investors, creditors and the government. The purpose of this writing is to determine the application of the Accurate application at PT Taxand Adi Consultama in producing reliable financial reports and to review its conformity with general accounting cycles and standards in accordance with theory and control aspects. The results of this paper show that implementing the Accurate application in the accounting process involves important steps, starting from the initial setup to using the available menus. Accurate effectively fulfills the principles of accounting theory, specifically accounting information systems, by making the accounting process simple, easy, accurate, and complete with the modules in it, and the features provided by Accurate make it possible to produce financial reports that comply with accounting standards. The evaluation results show that the application of the Accurate application at PT Taxand Adi Consultama can be carried out well, where this application provides modules that make it easier for users to input company transactions in order to produce reliable financial reports and produce reliable financial information output. The Accurate application can then be used by companies to improve control to avoid threats that may occur to the company and be used as a basis for making better business decisions. Keywords: Accurate, Financial Reports, Application Control